Limitations of Bedside Lung Ultrasound in Neonatal Lung Diseases - Liu, Xiaolei; Si, Shuyu; Guo, Yiyi; Wu, Hui (Frontiers in Pediatrics, 2022)
Lung ultrasound is a technique that has rapidly developed in recent years. It is a low-cost, radiation-free, and easy-to-operate tool that can be repeatedly performed at the bedside. Compared to chest X-ray, lung ultrasound has high sensitivity and specificity in the diagnosis of neonatal respiratory distress syndrome, transient tachypnoea of newborns and pneumothorax. Lung ultrasound has been widely used in neonatal intensive care units. However, due to the physical barriers of air, where ultrasonic waves cannot pass and therefore reflection artifacts occur, it has limitations in some other lung diseases and cannot fully substitute for chest X-rays or CT/MRI scanning. This review describes these limitations in detail and highlights that if clinical symptoms are not effectively alleviated after medical treatment or the clinical presentation is not compatible with the ultrasound appearances, then chest X-rays or CT/MRI scanning should be performed to avoid misdiagnosis and mistreatment.